Kebangkitan E-commerce Bertenaga AI: Mengubah Lanskap Bisnis di Tahun 2024 - Yema Charista Zelda; Bayu Ade Prabowo; Yuniarto Rahmad Satato (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The rapid adoption of artificial intelligence (AI) in e-commerce is revolutionizing the business landscape. This study explores the rise of AI-powered e-commerce and its impact on business models, strategies, and market dynamics in 2024. Through a multiple case study approach, focusing on leading e-commerce companies such as Amazon, Alibaba, and Shopee, the research reveals that AI is fundamentally transforming the way businesses operate in the digital economy. AI enables enhanced personalization, operational efficiency, and improved customer experiences, driving the emergence of new business models and competitive advantages. However, the adoption of AI also creates significant challenges, including implications for the workforce, ethical concerns surrounding data privacy and algorithmic bias, and potential impacts on market dynamics and competition. The study highlights the need for a strategic and ethical approach to AI adoption, collaboration among stakeholders, and adaptive regulatory frameworks. It concludes with recommendations for businesses, policymakers, and future research to navigate the transformative impact of AI in e-commerce. The findings contribute to the literature on digital transformation and disruptive innovation, offering valuable insights for managers, practitioners, and researchers.